Transition from ballistic to thermalized transport of metal-sputtered species in a DC magnetron. (14th December 2021) - Revel, Adrien; Farsy, Abderzak El; de Poucques, Ludovic; Robert, Jacques; Minea, Tiberiu
Abstract: Tunable diode-laser induced fluorescence technique has been optimized to accurately measure the titanium (Ti)-sputtered atom velocity distribution functions (AVDFs) in a magnetron discharge operating in DC mode. The high spatial and spectral resolution achieved reveals some features of the transport of the metal-sputtered atoms and their thermalization. The two groups of thermalized and energetic atoms have been very well separated compared to previous works. Hence, the fitting of the energetic atom group shows dumping from modified Thompson to Gauss distribution when the product pressure-distance from the target increases. In parallel, sputtered metal transport from the target has been simulated using the Monte Carlo collision (MCC) approach. Direct comparison between numerical and experimental results led to an improved cross-section for Ti–Ar momentum transfer, based on the ab initio formulas of the interaction potential derived from noble gas interaction. The accuracy of the experimental data enabled the numerical parametric study of the angular distribution and cut-off energy for the initial distribution of sputtered atoms to reveal the precise characterization of the initial conditions. A very good overall agreement is obtained for measured and calculated AVDFs. Comparison between the measured and modeling results emphasized the major role played by the argon (Ar) ions, not only in the sputtering process, but in the neutral metal transport by the gas rarefaction near the target. The microscopic description provided by the MCC model clearly reveals different transport regimes: ballistic, diffusive and back-scattering, which provide new insight into the thermalization of sputtered species in the intermediate pressure range.